Building Regulatory Capacity Assessment : Level 1 - Initial Screening - World Bank (Washington, DC: World Bank, 2017)
Urbanization is simultaneously a major driver of development, wealth creation, and poverty reduction, as well as one of the most pressing challenges of the 21st century. The building regulatory capacity assessment provides an important contribution to help cities and project managers working with development agencies to implement this last priority by offering a new resource to assess building and land use regulatory systems, and facilitate the collection of critical information about the building regulatory framework in any given city or country. The building regulatory capacity assessment is comprised of the level 1 - initial screening, designed for government officials and project managers undertaking rapid preliminary assessments. It provides an opportunity to initiate conversations with clients and relevant parties on strategies for achieving relevant development objectives. Level 1 is complemented by a level 2 - detailed exploration, which provides a set of guidelines for team members and contractors who are tasked with gathering and analyzing data and information about the building regulatory capacity of the target country, region, or municipality. Overall, the assessment identifies critical gaps, it provides the necessary information to develop a baseline for formulating technical assistance to clients, as well as drawing findings that can be used to determine areas for improvement and investment. As part of the building regulation for resilience program supported by the global facility for disaster reduction and recovery, the authors hope that this assessment tool will offer an effective resource for interventions within a wide range of urban development initiatives in cities of low and middle-income countries.